2017
DOI: 10.1016/j.trecan.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide: The Forgotten Child of Tumor Metabolism

Abstract: Nitric oxide (NO) is a signaling molecule with pleiotropic physiological roles in normal cells and pathophysiological roles in cancer. NO synthetase expression and NO synthesis are linked to altered metabolism, neoplasticity, invasiveness, chemoresistance, immune evasion, and ultimately to poor prognosis of cancer patients. Exogenous NO in the microenvironment facilitates paracrine signaling, mediates immune responses, and triggers angiogenesis. NO regulates posttranslational protein modifications, S-nitrosati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 93 publications
2
61
0
2
Order By: Relevance
“…NO in TME can be contributed by tumor cells or tumor-associated macrophages (Salimian Rizi et al, 2017). As stated already, melanoma cells expressed both iNOS and nNOS.…”
Section: Nitric Oxide Inflammatory Tumor Microenvironment (Tme) Andmentioning
confidence: 67%
“…NO in TME can be contributed by tumor cells or tumor-associated macrophages (Salimian Rizi et al, 2017). As stated already, melanoma cells expressed both iNOS and nNOS.…”
Section: Nitric Oxide Inflammatory Tumor Microenvironment (Tme) Andmentioning
confidence: 67%
“…A recent study has shown an increase of nitric oxide (NO) and inducible NO synthase (iNOS), which was suggested to be mediated by TLR-induced NF-κB signalling, in cervical samples from HR-HPV-infected patients [133]. Since NO is a critical component of the tumour microenvironment and promotes tumour angiogenesis, as well as tumour cell invasion and metastasis, it has been studied as a possible target for cancer therapy [134].…”
Section: Cellular Innate Immunity and Cancer Progression In Hpv Infecmentioning
confidence: 99%
“…Thus, the pentose phosphate pathway (PPP) would provide the reducing agent necessary for synthetizing NO. In hypoxic tumors, hypoxia inducible factor 1α (HIF‐1α) interacts with interferon‐gamma (IFN‐γ), thus inducing the expression of inducible NOS (iNOS) . NO produced and secreted by tumor cells reprograms stromal cells to support tumor progression, although high concentrations has been shown to induce apoptosis, and it also helps drug resistance and migration of cancer cells .…”
Section: Tumor Cells Metabolism: Beyond Warburg Effectmentioning
confidence: 99%
“…Moreover, NO modulates metabolism of tumor cells, inhibiting prolyl hydroxylase 2 (PHD2) and OXPHOS, hence promoting a glycolytic metabolism . Furthermore, S‐nitrosylation is a mechanism of posttranslational protein modification mediated by NO and implied in modulating the activity of several oncogenic‐signaling cascades and metabolic enzymes …”
Section: Tumor Cells Metabolism: Beyond Warburg Effectmentioning
confidence: 99%
See 1 more Smart Citation